1986
DOI: 10.1111/j.1699-0463.1986.tb03013.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTINOBACILLUS MURIS SP. NOV. ISOLATED FROM MICE

Abstract: Several unclassified strains were obtained during investigations of the aerobic pharyngeal flora of healthy white laboratory mice originating from four different colonies. Nineteen strains formed a group tentatively designated taxon 12. Comparative investigations including taxon 12, P. ureae sensu stricto. “P. ureae” strain Ackerman 80–443D, P. pneumotropica sensu stricto, P. pneumotropica type Heyl, P. pneumotropica type Henriksen and “H. influenzae‐murium” showed that taxon 12 was identical with “P. ureae” s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Phenotypic characters shared by all strains investigated (some included for genus-level separation; Table 1) were in accordance with the description of [A. ] muris (Bisgaard, 1986) except for variable reactions in acid formation from (2)-Dmannitol as well as variable reactions for indole production, urease and hydrolysis of aesculin. The a-glucosidase test (PNPG; 4-nitrophenyl a-D-glucopyranoside) was found to be positive.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Phenotypic characters shared by all strains investigated (some included for genus-level separation; Table 1) were in accordance with the description of [A. ] muris (Bisgaard, 1986) except for variable reactions in acid formation from (2)-Dmannitol as well as variable reactions for indole production, urease and hydrolysis of aesculin. The a-glucosidase test (PNPG; 4-nitrophenyl a-D-glucopyranoside) was found to be positive.…”
supporting
confidence: 62%
“…[Actinobacillus] muris was originally described based on 19 strains isolated from the oral cavity of healthy mice, with the provisional designation Bisgaard taxon 12 and the selection of a previously described reference strain (Ackerman80-443D T 5NCTC 12432 T ) as the type strain (Bisgaard, 1986) (Table S1, available in the online Supplementary Material). DNA reassociation studies showed that [A. ]…”
mentioning
confidence: 99%
“…For each colony morphotype, the highest scoring aligned sequence from the RDP database is associated with mice. Actinobacillus muris [43], L. murinus [44] and Staphylococcus saprophyticus [45] are murine commensal oral bacteria. Corynebacteria are commensals of the skin and mucous membranes of humans and animals, with C. mastitidis recently identified as an opportunistic infectious resident of the epidermis of laboratory mice [46].…”
Section: Discussionmentioning
confidence: 99%
“…16 S rRNA gene sequences from white colonies of cocci most closely align to uncultured bacteria assigned to the genus Streptococcus (designated S. unassigned). Five of the six species identified were shown previously to colonize mice (42)(43)(44)(45)(46), whereas Streptococcus thoraltensis has been found in rabbits (47). For comparisons with human oral microbiota, each consensus sequence was also aligned to the annotated Human Oral Microbiome Database 16 S rRNA reference sequences from the human oral microbiome.…”
Section: Caries Development and Recovery Of Bacteria-muc19mentioning
confidence: 99%